ANALISIS FAKTOR BRAND PERSONALITY MITSUBISHI OUTLANDER SPORT - Denny Raynaldi Dachlan; Herlin Hidayat (Prosiding Working Papers Series In Management, 2017)
The product of four-wheel vehicles in the market during this period is very much in number. Similarly, with various features offered by each manufacturer. Without asserting the differentiating value of a brand, of course, consumers will have difficulty to recognize a product. This difficulty will make it easier for consumers to move to other products. One way to explain the difference of a product is to know the brand personality of a product. This study aims to determine the factors that explain the brand personality of Mitsubishi Outlander Sport vehicles.This research uses factor analysis method to find brand personality from Mitsubishi Outlander Sport vehicle. Data collection method used in this study is clustered random sampling by spreading the questionnaire.The result of the research of the Mitsubishi Outlander Sport brand personality factor is 8 new factors that describe the brand personality of the Mitsubishi Outlander Sport vehicle. New factors generated in this study are smart and success, rational, online, imaginative and up-to-date, upperclass, outdoorsy, charming, and tough. Keywords: Factor analysis method